The Curious Incident of the Dog in the Night-Time Teaching Guide - Kansas State University, K-State First (My University, 2017)
This guide provides resources for faculty and staff at Kansas State University on the book "The Curious Incident of the Dog in the Night-Time" by Mark Haddon. Included in the guide are discussion questions, suggested classroom activities, other titles of interest, vocabulary, and additional resources.
Citation: K-State First (2017). The Curious Incident of the Dog in the Night-Time Teaching Guide [Brochure]. Manhattan, Kansas: K-State First.
Keywords: Curious Incident of the Dog in the Night-Time, The; Common reading program; Guide; First-year experience program